Public administration in the context of reflection of the modern innovative dig-ital level of economic development - Ovcharenko, Georgy V.; Petruk, Galina V.; Larkina, Natalia G.; Yalanskiy, Alexander P. (Nexo Revista Científica, 2021)
The article analyzes the state and society's interaction to achieve an innovative idea based on strategic thinking and culture, which determine justice in society, realize their behavior, and substantiate the importance of innovative digital technologies in a neo-information society determines a person as innovative. The research shows the necessity of innovative thinking among different-level managers able to create and manage innovative knowledge of personnel, creating innovative values. A practical vector of the transition of the economy to an innovation level is proposed.